Analisis Kewajiban Hukum Warga Negara Asing yang Menjalankan Bisnis di Indonesia Berdasarkan Undang-Undang Nomor 25 Tahun 2007 tentang Penanaman Modal - Flora Juniar Manik (Indonesian Journal Publisher, 2026)
This study aims to analyze the legal obligations of foreign nationals conducting business activities in Indonesia under Law Number 25 of 2007 on Investment, with a focus on assessing the clarity, scope, and enforceability of the regulatory framework in ensuring legal certainty and safeguarding national interests. The research employs a normative juridical method using statutory, conceptual, and comparative approaches to examine the structure and coherence of investment-related obligations within the broader system of Indonesian law. The findings reveal that although the Investment Law establishes fundamental obligations, including business entity formation, licensing requirements, compliance with national laws, corporate social responsibility, environmental protection, labor standards, and taxation, its regulatory formulation remains general and fragmented. The absence of clear normative boundaries, reliance on sectoral regulations, and broad administrative discretion create legal ambiguity and inconsistent enforcement practices. This condition not only complicates compliance for foreign investors but also weakens the principle of equality before the law and undermines legal predictability. The study concludes that clearer and more structured normative provisions within the Investment Law are necessary to strengthen legal certainty while maintaining a balanced relationship between investment facilitation and the protection of national legal sovereignty.